Text-centric approach in foreign language lessons - Ilyassova, G.O.; Ayazbayeva, A.M. (KSU Publ., 2020)
Nowadays, it is very important to develop skills in working with text, since the failure of students to master a particular science is often explained by their inability to work with them. They cannot isolate the basic semantic units, single out the most essential information, trace all levels of evidence, isolate the basic terms, etc. The text is, perhaps, the main educational-methodical unit of training. For the most complete and adequate use of it, the teacher needs to clearly imagine and then use the content and structural features of the text as the basis for the teacher and students to compose their own speech works in a foreign language. This article reveals the concept of text, provides a classification of the stages of working with text, provides techniques, and considers the nature, methodology and effectiveness of working with text in a foreign language lesson.
Мəтінге негізделген əдіс-тəсілдер шет тілдері сабағында
Текстоцентрический подход на уроках иностранного языка
Keywords: text; educational and methodological unit; text features; improvement of reading skills; reading literacy